PEMANFAATAN KERANJANG AJAIB TAKAKURA (TAKAKURA HOME COMPOSTING METHOD) DAN DAUR ULANG KREASI UNTUK MENGATASI MASALAH SAMPAH RUMAH TANGGA - Nyayu Neti Arianti; Melli Suryanti; Marlin . (DHARMA RAFLESIA, 2014)
This activity is carried out in Pantai Bajak Village, Teluk Segara, City of Bengkulu, with consideration the PKK organization is the most active in Teluk Segara. The targetaudience of this activity is the housewives who become member of PKK, in the hope thatapplied science and technology can be introduced particularly to housewives andgenerally to society. 14 audiences present and are excited to follow every stage of theactivity. Activities include outreach and direct practice with methods of Learning by doingto overcome household trash. Composted organic waste has been made by the TakakuraMagic Basket, and plastic waste is recycled into bags and aprons creations. The results ofan evaluation of the apllied technology shows that most participants strongly agreed toprovide an assessment of all aspects of the application of introduced technology, namelythe technical aspects of production (66.67%), economic aspects (73.81%), in terms ofaspects of innovation (73.81%) and aspects of behavioral change (82.14%). Thus the mostlikely introduced technology will be applied by the target audience.